A revolution in rice production? - Teng, Paul (2023)
To meet the increasing demand for rice worldwide, there is a need to revolutionise the way the crop is produced, which would also reduce the requirement for labour, improve water-use efficiency, and reduce greenhouse gas emissions. As presented at the International Rice Congress held in Manila on 16-19 October 2023, the prospect of achieving this is promising.